Transverse scattering characterization of refractive index sensor in tapered and untapered Photonic Crystal Fiber (PCF) / Siti Noraina Sanusidin, Mas Izyani Md Ali and Mohd Hanapiah Mohd Yusoff - Sanusidin, Siti Noraina; Md Ali, Mas Izyani; Mohd Yusoff, Mohd Hanapiah (Universiti Teknologi MARA Press (Penerbit UiTM), 2020)
This paper brief about the simulation of transverse scattering of liquid filled tapered and untapered Photonic Crystal Fiber (PCF) to function as a refractive index sensor. The simulation was conducted using Finite Difference Time Domain (FDTD) simulation for a wavelength range of 0.6 to 1.7 µm. The transverse scattering was correlated with the refractive index in the liquid filled PCF. It was investigated for untapered PCF with fiber outer diameter 125 µm and a series of tapered PCF from 90% until 10% of the original size. The transverse spectrum was analyzed using Principal Component Analysis (PCA) and the simulation results showed a correlation between the spectrum and the refractive index of liquid filled PCF. The sensitivity at singlewavelength and multiwavelength is proven to be 7.45 and 4.76 a.u/RIU respectively. The untapered PCF gives the most sensitive configuration for refractive index sensing application.